What We Don't Talk About When We Talk About Photography and Participation. (3rd July 2019) - Burbridge, Ben; Luvera, Anthony
Abstract: This conversation takes the work of artist Anthony Luvera as the basis for a broader analysis of participatory photography in the context of contemporary art. Where existing literature typically focuses on the ethics of participatory production – considering the amount of "agency" afforded to participants in any particular project – the discussion focuses instead on relationships between funders, facilitators, artists, audiences and participants in more material terms. It aims to open up an understanding of participatory photography, reflecting on the issues of financialization and labor typically overlooked in existing analyses and reflecting on some of the reasons for that omission.